Efektifitas Progressive Muscle Relaxation Terhadap Kecemasan Pada Pasien Kanker Payudara Yang Menjalani Kemoterapi - Ricky Z; Rini Rachmawaty; Yuliana Syam (Poltekkes Kemenkes Surakarta, 2018)
Backgound: Progressive Muscle Relaxation (PMR) exercise therapy is a focused therapy to maintain deep relaxation conditions. Empirical evidence has supported the use of Progressive Muscle Relaxation (PMR) in reducing headaches, insomnia, hypertension, and additional treatment in cancer patients and management of chronic pain. This article analyzes the effectiveness of Progressive Muscle Relaxation (PMR) in reducing anxiety and by reviewing the results of the current study. Method: This study explores quantitative evidence published in electronic database, such as Pubmed, Google Scholar, and ProQuest. By using electronic publications, we have identified 193 potential and relevant articles of interest while fifteen studies have been included in the final analysis. Results: the study shows that a significant improvement occurred in a post-intervention in reducing anxiety for participants receiving PMR compared to all control groups. Conclusion: The result indicates that PMR is a particularly useful supplementary treatment to reduce anxiety levels of cancer patients undergoing chemotherapy and nurses must be trained to perform Progressive muscle relaxation.